2012
DOI: 10.1007/s00723-012-0400-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Propylene Hydrogenation over Pt/Al2O3 by Parahydrogen-Induced Polarization

Abstract: Parahydrogen-induced polarization has been successfully used for a kinetic study of propylene hydrogenation over a Pt/Al 2 O 3 catalyst. It was shown that the reaction orders with respect to hydrogen are different for the pairwise and the non-pairwise hydrogen addition and are equal to 0.7 and 0.1, respectively. This observation of different reaction orders confirms the coexistence of different types of active sites which are responsible for the overall and the pairwise hydrogen addition to the propylene C=C d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…On the other hand, the Xe/N 2 mixture is inert relative to the catalyst operation (except the dilution of the reactants leading to decrease of their partial pressures). The 1 H polarization values increase in the presence of the buffering gas by 1.6 ± 0.1 fold (100% propane mixture vs 43% propane mixture) in the case of H 2 buffering gas (in agreement with previous studies 36,69 ), and by 1.4 ± 0.1 fold (100% propane mixture vs 43% propane mixture) in the case of Xe/N 2 (3:1) buffering gas, as shown in Figure 5c,f, respectively. We note that the actual increase in (initial) polarization of HP propane gas may be significantly greater because in the case of more dilute mixtures, HP propane has lower corresponding T LLS values (see Figure 5c,f), and therefore, likely experiences disproportionately greater polarization losses during more than 5−10 s of transport time from the reactor to the detector.…”
Section: ■ Methodssupporting
confidence: 91%
“…On the other hand, the Xe/N 2 mixture is inert relative to the catalyst operation (except the dilution of the reactants leading to decrease of their partial pressures). The 1 H polarization values increase in the presence of the buffering gas by 1.6 ± 0.1 fold (100% propane mixture vs 43% propane mixture) in the case of H 2 buffering gas (in agreement with previous studies 36,69 ), and by 1.4 ± 0.1 fold (100% propane mixture vs 43% propane mixture) in the case of Xe/N 2 (3:1) buffering gas, as shown in Figure 5c,f, respectively. We note that the actual increase in (initial) polarization of HP propane gas may be significantly greater because in the case of more dilute mixtures, HP propane has lower corresponding T LLS values (see Figure 5c,f), and therefore, likely experiences disproportionately greater polarization losses during more than 5−10 s of transport time from the reactor to the detector.…”
Section: ■ Methodssupporting
confidence: 91%
“…Another potential reason for T 1 and T S becoming longer is the greater fraction of HP propane in the gas phase as pressure increases due to changes in propylene hydrogenation kinetics. 56-57 Indeed, additional 1 H 400 MHz NMR measurements using the same experimental setup demonstrated that propylene to propane conversion increases as the total pressure increases (see SI). This fact is in agreement with typically positive overall reaction orders for hydrogenation of alkenes above 300 K. 56, 58-62 Notably, the experimentally determined ratio of T S / T 1 is nearly constant and amounts to 3.1±0.5 for all studied pressures, suggesting that the contribution of dipole-dipole interaction modulation towards the relaxation mechanism for hydrocarbons in general, and propane in particular, is significant.…”
Section: Resultsmentioning
confidence: 92%
“…Changing from H 2 to D 2 gave an isotope effect that was tempera ture dependent and varied from 1 to 2.7 but approached 1 at high temperature. When parahydrogen was substituted for ortho hydrogen, as in a parahydrogen induced polarization (PHIP) experiment, [18] polar ization transfer was observed from H 2 to propane. This means that both H atoms in a new product propane molecule came from the same molecule of H 2 .…”
Section: Introductionmentioning
confidence: 99%